2001
DOI: 10.1021/jf010492e
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycosides and Novel Iridoid Glycoside from the Leaves of Morinda citrifolia

Abstract: One new iridoid glycoside and five known flavonol glycosides have been isolated from the leaves of Morinda citrifolia. The new iridoid exists as an epimeric mixture in solution. Complete assignments of the proton and carbon chemical shifts for the individual epimers were accomplished on the basis of high-resolution 1D and 2D NMR data. Their antioxidative activities were measured. All of these compounds showed DPPH free radical scavenging activity at the concentration of 30 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 14 publications
(17 reference statements)
3
62
0
2
Order By: Relevance
“…Chromosomal stickiness values were 0.5% in negative control and 3.25% in posi- As such M. citrifolia aqueous extracts have protective effect against the oxidative damage induced by H 2 O 2 . This protective effect may be due to the anthraquinones present in M. citrifolia leaves (Sang et al 2001, Zin et al 2006. Recent studies revealed the antigenotoxic effects of noni juice against the chromosomal aberration and sister chromatid exchange induced by a chemotherapeutic agent, mitomycin C (MMC) in human lymphocytes (Treetip et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal stickiness values were 0.5% in negative control and 3.25% in posi- As such M. citrifolia aqueous extracts have protective effect against the oxidative damage induced by H 2 O 2 . This protective effect may be due to the anthraquinones present in M. citrifolia leaves (Sang et al 2001, Zin et al 2006. Recent studies revealed the antigenotoxic effects of noni juice against the chromosomal aberration and sister chromatid exchange induced by a chemotherapeutic agent, mitomycin C (MMC) in human lymphocytes (Treetip et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These mice remained tumor-free for their entire lifespan. Two months later, four tumor cell-resistant mice from the fNE and BuOH groups were rechallenged with 5x10 6 live S180 tumor cells/mouse i.p. The mice completely rejected this second tumor cell challenge, indicating that an effective immune response had been activated.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of major natural products have been identified in the noni plant thus far (1,2). Two novel glycosides and a new unusual iridoid, known as citrifolinoside, isolated from noni were shown to have an inhibiting effect on activator protein-1 (AP-1) transactivation and cell transformation in the mouse epidermal JB6 cell line (3)(4)(5)(6)(7). Although its traditional uses primarily involved topical application of leaves and roots, the noni fruit has been more popular for modern usage (8).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonol glycosides appear to predominate in M. citrifolia L. leaves; rutin and other flavonol glycosides have previously been identified in raw M. citrifolia L. leaves (Sang et al, 2001a). However, the presence of flavonol aglycones in M. citrifolia L. leaves has not been previously reported.…”
Section: Fig 1 Unripe Fruitmentioning
confidence: 91%
“…Previous phytochemical studies revealed that M. citrifolia L. leaves contain a variety of phytochemical constituents, including terpenoids (Ahmad & Bano, 1980;Saludes et al, 2002;Takashima et al, 2007) phytosterols, fatty acids and their glycosides (Takashima et al, 2007) iridoids and their glycosides (Sang et al, 2001 a,b,c,d;Sang et al, 2003) and flavonol glycosides (Sang et al, 2001a).…”
Section: Fig 1 Unripe Fruitmentioning
confidence: 99%